Entropy Generation Study on Natural and Forced Convection of Nanofluid Flow in Vertical Channels - S. E. Ghasemi; A. A. Ranjbar (Engineering Reports, 2025)
ABSTRACT In the present research, the entropy generation (EG) for a nanofluid through vertical channels is analyzed numerically. The water‐based suspension of alumina nanoparticles with different volume fractions is considered a heat transfer fluid. The nanofluid flow in the channel is under the effects of forced and natural convection simultaneously. For EG assessment, the values of EG number, Bejan number, EG ratio, and average EG number are evaluated comprehensively. The effect of changes in some parameters including Brinkman (Br) number, temperature difference, and concentration of nanoparticles in EG evaluation will be assessed. The results show that by increasing the temperature difference, the EG number is enhanced. Also from the results, the Bejan number increases by reducing the temperature difference.